Molecular Typing and Phylogenetic Analysis of Cutaneous Leishmania from Iraqi Patients (Medico Legal Update, 2020)
This study aimed for molecular characterization of local isolates of L. tropica and L. major and theirrelatedness to reference isolated from neighboring countries. Exudates and dermal tissues were collectedfrom the cutaneous lesions of 50 newly diagnosed patients with CL. Leishmania DNA was extracted fromlesion exudate and 5.8S rRNA gene was amplified using two sets of specific primers through nested PCR. Atotal of 12 PCR products were directly sequenced and the resultant sequences were aligned with referencesequences in National Center for Biotechnology Information (NCBI). A phylogenetic tree was constructedfor local Leishmania isolates with the reference isolates using Mega 6 software. According to alignmentresults out of 12 sequences, 9 sequences were belonging to L. major, while 3 sequences were belonging toL. tropica. All local L. major isolates were very close to reference isolate KP773404.1 (an Iranian isolate),while all local L. tropica isolates were very close to reference isolate KY612611.1 (an Iranian isolate) withan identity of 98%. Phylogenetic trees confirmed that closest isolates for local Leishmania (whether L.tropica or L. major) was the Iranian isolate. These data indicate that local isolates of L. tropica and L. majorare closely related to Iranian isolates.